IMPACT OF MATERNAL WEIGHT GAIN AND INFLAMMATORY MARKERS ON NEONATAL IRON DEFICIENCY: A CROSS-SECTIONAL STUDY FROM A PEDIATRIC PERSPECTIVE - Santosa, Qodri; Oliviany, Windy; Hafiidhaturrahmah, Hafiidhaturrahmah; Pratidina, Wening Gelar; Hapsari, Ariadne Tiara; Priyanto, Edy; Muntafiah, Alfi (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Background: Maternal health during pregnancy is crucial for neonatal outcomes, particularly regarding iron status. This study investigates the impact of maternal weight gain and inflammatory markers on neonatal iron deficiency in a cohort of mothers and their newborns. Methods: A cross-sectional study was conducted involving spontaneously delivered infants from single, full-term pregnancies, with Apgar scores ≥7 at the first minute and normal birth weights (≥2,500 to <4,000 grams). Maternal weight gain was categorized as